ANALISIS POTENSI DAN DISTRIBUSI SERTA STRATEGI PENGEMBANGAN KOMODITAS MELATI GAMBIR DI KECAMATAN RAKIT KABUPATEN BANJARNEGARA - Sarno; Eko Apriliyanto (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2016)
Gambir Jasmine is one of the unique and rare commodities, it is only found in the Rakit Subdistrict Banjarnegara Regency. The difference potential of each village in producing jasmine gambir commodity causes differences in the distribution of the commodities its produces. It means that there is a gambir jasmine commodities evenly distributed in each village and there are concentrated in one village. The research that is important about potential and distribution analysis, development and implementation strategy of commodity growth centers gambir jasmine and potential area of ​​its development so that commodities of gambir jasmine can be supreme and mainstay commodity in Rakit District Banjarnegara Regency. The aim of this research is to analyze the potential and distribution of Gambir Jasmine as a mainstay commodity on each village, determine commodity distribution and development strategy of gambir jasmine areas in Rakit subdistrict. This research was conducted by using survey method with main target is all farmer of gambir jasmine in Rakit District. The data analysis used Location Quotient, Shift Analysis, Super Impose, analysis of localization and specialization coefficient. The result shows that all villages in Rakit District have potential for development gambir jasmine as mainstay commodity, distribution commodity it’s spread all over villages in Rakit Subdistrict so that comparative advantages could be known or different. In addition all villages in Rakit Subdistrict don’t have certain event to develop gambir jasmine. Based on SWOT analysis so that analysis produced gambier jasmine development strategies in Rakit. Keywords : Banjarnegara, distribution, potential, strategy